Dependence of resistivity of electrodeposited Ni single layer and Ni/Cu multilayer thin films on the film thickness, and electron mean free path measurements of these films - Gholamreza Nabiyouni (Iranian Journal of Physics Research, 2007)
The Boltzmann equation is a semiclassical approach to the calculation of the electrical conductivity. In this work we will first introduce a simple model for calculation of thin film resistivity and show that in an appropriate condition the resistivity of thin films depends on the electron mean free path, so that studying and measurement of thin films resistivity as a function of film thickness would lead to calculation of the electron mean free path in the films. Ni single layers and Ni/Cu multilayers were grown using electrodeposition technique in potentiostatic mode. The films also characterized using x-ray diffraction technique and the results show at least in the growth direction, the films were grown epitaxially and follow their substrate textures.